PENINGKATAN KEMAMPUAN MENULIS ANGKA 1-10 MELALUI MEDIA PASIR KINETIK PADA ANAK USIA 4-5 TAHUN DI TK TUNAS RIMBA JAMBEWANGI - Putri Adista Setiani; A. Zulkarnain Ali; Wedya Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The ability to write numbers in children aged 4-5 years at Tunas Rimba Jambewangi Kindergarten is still low, with 37.5% of children below the standard (BB/MB). The cause is the conventional learning method which is monotonous and less interesting. Kinetic sand was chosen as an alternative media because it can stimulate children's fine motor skills, cognitive, and creativity, as well as provide a fun learning experience. By using the classroom action research (CAR) method, this study aims to determine how effective kinetic sand media is in improving the ability to write numbers 1-10 in children aged 4-5 years. It was carried out in two cycles, with planning, action, observation, and reflection as its components. The research sample was 16 children aged 4-5 years at Tunas Rimba Jambewangi Kindergarten. The results of the study showed that in the pre-cycle 62.5% of children reached the BSB/BSH criteria, while 37.5% were still below the standard (BB/MB). In Cycle I, there was an increase with 81.25% of children reaching BSB/BSH, but there were still children who had difficulty distinguishing numbers. In Cycle II, there was a significant increase by modifying the kinetic sand media, namely, 93.75% of children achieved BSB/BSH, and children were more enthusiastic, independent and able to write numbers correctly. It can be concluded that kinetic sand media has been proven effective in improving the ability to write numbers 1-10 in children aged 4-5 years.